Towards a measuring framework for knowledge creation in smart cities (2020)
This article investigates the implications of general models of smart sustainable cities (SSC) on the indicators and measurement frameworks that we use to study them. We first investigate the mainstream theory of SSC and their corresponding measurement frameworks. From the analysis, we show that such frameworks do not address the dynamic behaviour of cities. We then explore knowledge based smart sustainable cities, as an alternative theory of SSC, and investigate the measurement frameworks derived from this theory. We show that, despite having a different approach, these measurement frameworks still depend on static indicators and promote static view of the city. We then conjecture that this is due to fussy definitions of knowledge and incomplete investigations of the implications of latest theories of knowledge over the structure and strategy of smart cities. Finally, we propose a set of premises and principles that will improve the theory of Knowledge based smart sustainable cities (KBSSC) and show how this new definition will affect the design of indicators and measurement frameworks in a KBSSC.